Application of the Seal of Responsible Tourism in the means of accommodation in times of pandemic: a study in Natal-RN, Brazil (Revista Brasileira Multidisciplinar, 2024)
The Natal-RN destination (Brazil) was the second most relevant in the Northeast region in relation to the adoption of the Responsible Tourism Seal, created by the Ministry of Tourism so that the sector's production chain could resume its activities amid the 2020 pandemic scenario. Around 520 providers of tourist services in the locality requested the issuance of the certification. In view of this, the present research aims to analyze the application of the Responsible Tourism Seal program in accommodation facilities in the destination Natal-RN, based on the need to explore the tourist situation regarding compliance with measures to combat the transmission of Covid-19 during the carrying out their activities. To this end, the exploratory-descriptive research, of a qualitative nature, approached managers of five accommodation facilities in the destination, through the application of semi-structured interviews. The results obtained expose the disparity between the implementation of the program prepared by the Ministry of Tourism and the certification acquired, on its own initiative, through accommodation that is part of a large network present in the evaluated enterprises. In view of the above, it is recommended that sporadic inspections be implemented in enterprises that obtain the seal, in order to guarantee excellent service to tourists. The present investigation is relevant due to the need to explore the real scenario regarding compliance with measures to combat the transmission of coronavirus during the exercise of tourist activities, especially due to its potential for worsening with the possible movement of variants between different destinations.
Keywords: Covid-19; Responsible Tourism Seal; Certifications; Accommodation facilities; Natal-RN